Pervious pavement blocks made from recycled polyethylene terephthalate (PET): Fabrication and engineering properties - Ryu, Byung Hyun; Lee, Sojeong; Chang, Ilhan (Sustainability (Switzerland), 2020)
The importance of permeable and pervious pavements in reducing urban stormwater runoff and improving water quality is growing. Here, a new pervious pavement block material based on recycled polyethylene terephthalate (PET) waste is introduced, which could contribute to reducing global plastic waste via PET's utilization for construction material fabrication. The engineering properties and durability of recycled PET aggregate (RPA) pervious blocks are verified through flexural tests, in situ permeability tests, clogging tests, and freeze-thaw durability tests, and their cost-effectiveness is assessed by comparison with existing permeable/pervious pavers. Their engineering and economic characteristics confirm that the RPA pervious blocks are suitable for use in urban paving.
Keywords: Flexural strength; Freezing and thawing; Permeability; Pervious pavement block; Recycled PET aggregate (RPA) block